The use of smartphones among the rural micro-entrepreneurs in Negeri Sembilan - Megat Tajudin, Putri Noorafedah; Idris, Khairuddin (Faculty of Educational Studies, Universiti Putra Malaysia, 2019)
Although empowerment is important and valuable to eradicate poverty, there is little research on how smartphones have played a role in assisting it to become a reality. The purpose of this research is to explore the usage of smartphones among rural micro-entrepreneurs towards their empowerment. Therefore, using face to face in-depth interviews, online interviews, document analysis and observations techniques, this research explores how smartphones have made a difference to the rural micro-entrepreneurs' business. The research participants were five (5) micro-entrepreneurs from rural districts in Negeri Sembilan, Malaysia. They were previously the participants of 2 Years Exit Programme under Department of Social Welfare of Malaysia. They run small and medium enterprises such as groceries shop, food stalls, coconut milk seller, tailoring and perfume company founder. The research found that regardless of the low level of education, type of businesses or physically disabled condition of the micro-entrepreneurs, it does not stop them to learn how to utilise smartphones for their business needs. Smartphones and the internet have empowered rural micro-entrepreneurs by enabling them to reach out to customers outside their locality and increase their marketing power. They also used the internet and smartphones as an educational and information resource namely from Google and Youtube. The research found that the participants mostly use social networks such as WhatsApp and Facebook for business purposes. The reasons for using smartphones are influenced by others and the intention to use it for business. Smartphones positively benefit their business as it improves the way of communication in business and life and enhanced their business marketing and sales. However, it also means they are dependent on smartphone and the internet to facilitate their business tasks involving communication and advertising. To facilitate the uptake of this affordable yet important smartphone technology, it is recommended that the key stakeholders' organisations study adult education concepts in attracting and engaging the rural micro-entrepreneurs to embrace technology. It is important to understand some basic principles about how adults prefer to learn, especially on new knowledge, skills and gadgets. Government agencies, NGOs and social movement bodies can contribute by organising and engaging in digital empowerment programs for the rural micro-entrepreneurs leveraging their access to digital commerce, internet marketing and such.